(untitled) (MAUSAM, 1970)
Theory of calculating the displacement in a general viscoelastic medium, generated by an arbitrary pressure applied on the surface of a spherical cavity have been developed. In particular, three types of pressures have been considered and the corresponding displacements in Maxwell as well as Voigt type viscoelastic media have been derived. As special cases, the results of earlier authors in elastic medium have been deduced and compared. The results obtained have been discussed.